Reading on Screen Vs Print: An Investigation into the Attitudes of Moroccan EFL University Students - TAKY-EDDINE, omar; Madaoui , Redouane (International Journal of Language and Literary Studies, 2022)
This study was conducted with the objective to explore University students' attitudes toward onscreen reading and the factors affecting their attitudes. A descriptive survey was used in this study as a data collection tool. The questionnaire results of 212 students belonging to Ibn Zohr University, Faculty of art and humanities, have asserted that Moroccan EFL university students have positive attitudes toward onscreen reading. However, the participants also revealed several negative factors that make their onscreen reading experience challenging and troublesome. Overall, this study revealed five positive and negative factors affecting students' attitudes toward onscreen and print reading. These include practical factors, psychological factors, economic factors, cognitive factors, and health factors. The pedagogical implications discussed in this study are valuable and worth considering by students, teachers, decision-makers, and curriculum designers.